2020
DOI: 10.4103/ijcm.ijcm_236_19
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-care activities: A community-based survey in an urban slum in Hyderabad, India

Abstract: Background: Diabetes is a chronic illness with silent manifestations, which can be better managed by the individual through self-care behaviors such as diet control, proper exercise, monitoring blood glucose, and adherence to dug. Objective: The present study was conducted to assess the prevalence of existing self-care behaviors among people with diabetes and its associated factors. Methods: It was a community-based, cross-sectional study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Interestingly, a study conducted in a tertiary care center in the KSA and another study by Almomani et al also found that the lowest score was in exercise sessions and the highest score on the medication adherence scale; however, their scores were slightly higher than the present study in most of the subscales [ 21 , 30 ]. Even though a community-based survey conducted in India among diabetes patients showed similar trend findings across the subscales of self-management behavior, their participants’ overall scores were lower than our study [ 31 ]. We identified the major area of concern in self-care management, which is regular exercise, an essential component of self-care behavior that is to be followed.…”
Section: Discussioncontrasting
confidence: 60%
“…Interestingly, a study conducted in a tertiary care center in the KSA and another study by Almomani et al also found that the lowest score was in exercise sessions and the highest score on the medication adherence scale; however, their scores were slightly higher than the present study in most of the subscales [ 21 , 30 ]. Even though a community-based survey conducted in India among diabetes patients showed similar trend findings across the subscales of self-management behavior, their participants’ overall scores were lower than our study [ 31 ]. We identified the major area of concern in self-care management, which is regular exercise, an essential component of self-care behavior that is to be followed.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous research amongst Asian young adults in China and Singapore recognized that adherence to diabetes medication is poorer in younger adults than in older adults [28]. Researchers found similar results in urban slums in South India, where the overall prevalence of self-care activities was low, indicating a need for more awareness and education about diabetes self-care management [38]. South Asian populations with T2D have been shown to experience these barriers to self-care activities, including communication discordance, lack of knowledge and misperceptions about the condition and management, gender-specific roles, lack of family support and cultural appropriateness [39].…”
Section: Discussionmentioning
confidence: 82%
“…Higher age was associated with better self-management in nine studies—the consistency of findings, despite most studies being moderate quality suggested reasonable confidence in the evidence. There was limited evidence of an inverse association from three studies for exercise, self-monitoring and foot care in diabetes [ 36 , 41 ], and for medication adherence in patients undergoing stroke recovery [ 49 ]. Two of these studies used higher age cutoffs (≥60, ≥70 years) suggesting that the relationship between age and self-management could be non-linear [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…being less educated was associated with higher self-management) was a low-quality study based on a small study sample (n = 150) [ 74 ]. Studies that observed multiple self-management behaviours reported mixed findings, with education inversely associated with exercise, diet and foot care [ 36 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation